Benefit of cochlear implants in adult individuals with prelingual deafness - Barreto Giorgi Sant’Anna, Sandra; de Oliveira Eichner, Andréa Cristina; Cardoso Guedes, Mariana (O Mundo da Saúde, 2008)
The indication of cochlear implants for patients with pre-lingual loss, both adolescents and adults, was always very controversial due to the fact that most studies show little or no benefit in the open set speech recognition. It is necessary to review this concept, reorganizing pre-implant evaluation, emphasizing language evaluation, social insertion and expectation. This work aims to evaluate the benefits young adults with prelingual deafness have after cochlear implant, considering not only the results in speech perception tests, but also the subjective impressions of patients in relation to the changes in quality of life. This is a transversal retrospective clinical study. We evaluated the results of speech perception tests and the subjective perception of quality of life after the constant use of cochlear implants of eleven young adults with prelingual deafness and submitted to surgery for implantation. Only two individuals presented an open-site speech recognition at a rate of 50% or more. All individuals were able to recognize their own names and to discriminate suprasegmental aspects. Some patients with long-standing prelingual deafness develop auditory abilities and have a good performance in open-set speech recognition. However, even those not capable of reaching these results say to be satisfied with the device and recognize an improvement in quality of life.